The Church Bells of Linlithgowshire (Proceedings of the Society of Antiquaries of Scotland, 1913)
Sometimes bells were multiplied in a church tower without regard to the musical relation of their notes, such a collection of bells being rung together at haphazard, or the single bells used separately. Another method was to cast a large number of small bells upon which tunes could be played. After the Reformation period there was a great development on the Continent of these musical bells, the sets of which are known as carillons : the bells themselves were fixed " dead," as it\r is called, and struck by hammers operated by a system of wires attached to a row of keys or levers. A few of these are known in larger Scottish churches. As far as bells are concerned, Scotland has till recently been Continental in practice, and\r little, if at all, influenced by England. In Linlithgowshire there are twelve old churches, or churches representing old churches, in which ancient bells remain or\r in which they could have survived and six with modern bells.